2015
DOI: 10.1016/j.bmc.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activities of halogenated pyrrolo[3,2-d]pyrimidines

Abstract: In vitro evaluation of the halogenated pyrrolo[3,2-d]pyrimidines identified antiproliferative activities in compounds 1 and 2 against four different cancer cell lines. Upon screening of a series of pyrrolo[3, 2-d]pyrimidines, the 2,4-Cl compound 1 was found to exhibit antiproliferative activity at low micromolar concentrations. Introduction of iodine at C7 resulted in significant enhancement of potency by reducing the IC50 into sub-micromolar levels, thereby suggesting the importance of a halogen at C7. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…This was followed by a modified Batcho-Leimgruber indole synthesis to prepare enamine 3 . [9] The Batcho-Leimgruber process relies on the slight acidity of the 6-methyl group, which can be deprotonated to form a carbocation that is resonance stabilized by the nitro group. Nucleophilic attack on the dimethylacetal reagent results in formation of the amino side chain, which is deprotonated to result in the elimination product 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was followed by a modified Batcho-Leimgruber indole synthesis to prepare enamine 3 . [9] The Batcho-Leimgruber process relies on the slight acidity of the 6-methyl group, which can be deprotonated to form a carbocation that is resonance stabilized by the nitro group. Nucleophilic attack on the dimethylacetal reagent results in formation of the amino side chain, which is deprotonated to result in the elimination product 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[9] A structure-activity relationship (SAR) study found that compound 5 is a potent inhibitor of the TNBC MDA-MB-231 cell line, and further, caused an accumulation of cells in the G 2 /M stage without causing significant apoptosis. [9] These findings are consistent with earlier reports of other 9-deazapurines finding use as antiproliferative agents. [12] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focussing on the biological potential of fused pyrimidinones, and continuing our work on the synthesis of new N‐heterocycles, we intended to further capitalize on the CF rDA protocol by synthesizing more complex pyrimidinone‐fused moieties in both racemic and enantiopure forms. Pyrrolopyrimidines have a wide range of applications in medicinal chemistry; they show antimicrobial, antitumor, antiasthmatic, antihypertensive, and anti‐inflammatory activities. Pyrimidoisoindoles show high vasorelaxtant,[26a] antiplasmodial,[26b] and antifungal actions.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrolopyrimidines display a broad applicability in medicinal chemistry exhibiting antimicrobial [ 39 , 40 , 41 , 42 , 43 ], antitumour [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], antiasthmatic [ 59 ], antihypertensive [ 60 ], and anti-inflammatory [ 61 ] activities. Several method have been developed for synthesizing pyrrolopyrimidines in the last few years [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%